2009
DOI: 10.1007/s11432-009-0173-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective PID control for non-Gaussian stochastic distribution system based on two-step intelligent models

Abstract: A new method for controlling the shape of the conditional output probability density function (PDF) for general nonlinear dynamic stochastic systems is proposed based on B-spline neural network (NN) model and T-S fuzzy model. Applying NN approximation to the measured PDFs, we transform the concerned problem into the tracking of given weights. Meanwhile, the complex multi-delay T-S fuzzy model with exogenous disturbances, parametric uncertainties and state constraints is used to represent the nonlinear weight d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…By solving a series of LMIs (9), (19), (20), the new PI control gains K P 1 , K P 2 and K I can be computed as K P 1 = −0.9459, K P 2 = −1.0523, K I = 56.1426…”
Section: Numerical Solutions Of Pi Gains and Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By solving a series of LMIs (9), (19), (20), the new PI control gains K P 1 , K P 2 and K I can be computed as K P 1 = −0.9459, K P 2 = −1.0523, K I = 56.1426…”
Section: Numerical Solutions Of Pi Gains and Simulation Resultsmentioning
confidence: 99%
“…However, in these results a nonsingular constraint related to well-posedness should be guaranteed, which might result in non-convex algorithms and conservative outcomes. For the shape control of the output stochastic distribution, the improved PI controller design based on a series of convex LMI optimization algorithms was developed in [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in order to optimize the dynamical tracking performance for the interference term " d 2 ðtÞ, the peak-to-peak control gain is used (see Scherer and Weiland 21 and Yi et al 39 ), which is defined as follows…”
Section: Design Of Controlled Input With Disturbance Observermentioning
confidence: 99%
“…Then, by smoothly blending those local linear models together with designed membership functions, the overall T-S models of nonlinear dynamics can be successfully obtained. It has been shown that many physical nonlinear control systems can be modeled and analyzed using T-S fuzzy models, such as networked control systems, 33 chaotic systems, 34 descriptor systems, 35 stochastic systems, 36 time-delay systems, 37 and so on. Inspired by the above observations, this article aims to investigate the disturbance estimation and rejection problem for yaw channel model of a small-scale UAV helicopter with unknown mismatched disturbances.…”
Section: Introductionmentioning
confidence: 99%